Influence of Temperature and Purity of Polyacrylic Acid on its Adsorption and Surface Structures at the ZrO/Polymer Solution Interface - M. Wiśniewska; S. Chibowski (Adsorption Science & Technology)
The influence of temperature and the effect of the purity of polyacrylic acid (PAA) on its conformation on the zirconium oxide surface were studied. Spectrophotometric measurements, potentiometric titrations, electro-kinetic and viscosity measurements allowed the determination of the amounts of polymer adsorbed, the surface charge and the zeta potential of solid particles in the absence and presence of the polymer together with the thickness of the polymer adsorption layers. All measurements were carried out over the temperature range 15—40°C. The occurrence of a minimum in the adsorption of PAA between 25–30°C was caused by conformational changes of the polymer macromolecules. For non-filtered PAA, a decrease in polymer adsorption and an increase in the thickness of the adsorbed polymer layers were observed. These result from changes in the polydispersity index of filtered PAA and the blocking of some active sites on the oxide surface by inorganic contamination present in the non-filtered PAA samples. The free energy of PAA adsorption was calculated from the zeta potential data. Some parameters characterizing the conformation of PAA chains in the bulk liquid phase and on the ZrO 2 surface were determined.